Dispositivos computacionais e paralisia cerebral: uma revisão de literatura - Oliveira, Amanda Bueno de (Universidade Federal de São Carlos, 2021)
Introduction: Upon the advances on the use and development of technologies over the past decades, the access to the computer has been expanded and employed as a tool for literacy, socialization, leisure, communication, memory and ensuring greater accessibility and autonomy to users with disabilities, such as cerebral palsy. Distinct software and hardware adaptations can be implemented to guarantee that, taking notice of solutions that best adjust to the individual’s skills and the settings that surround their daily life, as the clinic, home and school. Knowing that the computer can be employed as Assistive Technology (AT) or accessed through an AT device, and understanding the potencial these interactions hold, one of the qualified professionals to mediate the selection and training in the use of the selected resources is the occupation therapist. Aim: This study aimed to identify in the national and international literature how the use of computing devices by cerebral palsy users is depicted, comprehending the stipulated goal of the user’s computer use in the intervention process and which devices mediate that access; another objective was identifying the participation of Occupational Therapy in the studies. Methods: Being described as a systematic review of the literature, the search occurred in March of 2021, detecting records published from 2016 to 2020, through the Portal de Periódicos da CAPES and SciELO databases; the articles were screened based on PRISMA guidelines. Results: A total of 102 articles were identified, considering the chosen keywords in portuguese and english, amongst those, 31 records were in the review’s final sample. The texts brought devices and sensors that captured and evaluated the appendicular movement, gaze-based movement and electromagnetic waves as computer access devices, focused on the user’s rehabilitation and communication process. Discussion: Technology’s fast evolution enables it’s continuous adaptation in order to better meet the needs of each user, facilitating their engagement by connecting them with society and presenting a wide range of interactive and accessible activities that permit their autonomy, especially when combined with the training of the device’s use and the inclusion of the user during the process of choosing the device and their objectives towards it. Conclusion and final considerations: Although the study’s limitations, it was possible to see the overall picture of computing device’s use with people with cerebral palsy, unfolding not only the potential of such technologies, but also the adjustments that are still in development to further expand their accessibility.
Computer devices and cerebral palsy: a review of the literature
Keywords: Sistemas computacionais; Paralisia cerebral; Tecnologia assistiva; Terapia ocupacional; Revisão de literatura; Computer systems; Cerebral palsy; Assistive technology; Occupational therapy; Literature review; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL